Upper limb muscle-bone asymmetries and bone adaptation in elite youth tennis players - Ireland, A.; Maden-Wilkinson, T.; McPhee, J.; Cooke, K.; Narici, M.; Degens, H.; Rittweger, J. (Medicine & Science in Sports & Exercise, 2013)
Introduction: The study of tennis players allows the nonracket arm to act as an internal control for the exercising racket arm. In addition, the study of the upper limbs removes the influence of gravitational loading, allowing the examination of the influence of muscular force on bone adaptation.